Pengembangan Bandara Waterbase Pesawat Terbang Laut Sebagai Penunjang Wisata di Pulau Tinabo, Kepulauan Selayar, Sulawesi Selatan - Idham Sri Yusyarif; Shirly Wunas; Ganding Sitepu (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2023)
Tourism is one of the strategic sectors that drives the wheels of the economy with a large contribution. To strengthen tourism development, it needs to be supported by adequate transportation access. The aims of this study were 1) to analyze the tourism potential of the island and the potential for developing sea planes for tourist transportation on Tinabo Besar Island, 2) to explain the oceanographic and meteorological conditions that could support sea plane flights, and 3) analyzing the appropriate spatial dimensions for developing seaplane tourist transportation on Tinabo Besar Island, Takabonerate National Park, Selayar Islands district. Sources of data for this research come from BMKG documentation, BPS 2020-2021, and from the 2021 Takabonerate National Park Office as well as direct surveys at the research site and interviews with Banyuwa Management, Takabonerate Hall, and API Banyuwangi. This study uses descriptive, comparative and spatial analysis. The results showed that: 1) Tinabo Besar Island which has Takabonerate National Park has great potential for island tourism development, and is suitable for the development of seaplane-based tourism transportation 2) Oceanographic and Meteorological conditions of Tinabo Besar Island are feasible for seaplane-based tourist transportation, based on the results of BMKG data, and 3) the proper spatial dimension for developing seaplane tourism transportation on Tinabo Besar Island is the area of ​​seaplane takeoff and landing operations plus the wide zone of utilization zone of Tinabo Besar Island, namely 5.06 km2 + 9, 73 km2 so that the total area is 14.79 km2. The spatial dimensions of Tinabo Besar Island are suitable for planning seaplane landing and take-off sites. However, for the wharves it is necessary to test the resilience if it is developed as a seaplane mooring area, and is equipped with several supporting equipment, such as fire extinguishers, safety equipment, lights, airbags, and improving the skills of the personnel on duty.